PENGARUH POSISI KAS, RASIO UTANG TERHADAP EKUITAS,DAN POTENSI PERTUMBUHAN TERHADAP RASIO PEMBAGIAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Indayani Indayani; M Nur Yahya (Faculty of Economic and Business, 2013)
The aim of this study is to determine and examine the influence of cash position, debt to equity ratio, and growth potential to the dividend payout ratio of companies listed in Indonesia Stock Exchange (BEI). The analysis method of the data used to test the hypothesis is the multiple linear regressions. The test result showed that simultaneous cash position, debt to equity ratio, and growth potential did not significantly influence the dividend payout ratio at manufacturing companies listed on the BEI. The test results showed that only partially variable cash position that significantly influence the dividend payout ratio of companies listed on the Stock Exchange, while variable debt to equity ratio, and growth potential does not affect the dividend payout ratio of companies listed on the BEIDOI: 10.15408/etk.v12i1.1904